Bouncing back from Workplace Stress: From HRD's Individual Employee's Developmental Focus to Multi-facetted Collective Workforce Resilience Intervention. Issue 4 (November 2020) - Mendy, John
The Problem: Human resource development (HRD) research has sought to demarcate a human developmental problem by identifying learning interventions through which individuals can contribute towards group and organizational growth. However, there remains the fundamental problem, which is how to go beyond individualized employee development to a more collective resilience model building against workplace stress. Such lesser effectiveness has led to financial, emotional and psycho-social costs to individuals and collectives. Based on the theoretical analysis of human capital theory, HRD research and literature are lacking in how to more effectively operationalize collective resilience against workplace stress. The Solution: A multi-faceted collective workforce resilience intervention conceptual model is proposed to enable both management and employees to overcome ineffective implementation of human development and thereby bounce back from workforce stress. Four aspects of the model's practical operationalization are proposed as steps to help the HRD community of practitioners and scholars to engrain resilience as a workplace culture in resolving stress. Implications on (1) the identification of workplace stress, (2) the effective design and operationalization of development capacities. (3) the resilience intervention initiatives, and (4) the management of collective workforce resilience are highlighted. The Stakeholders: The proposed model is designed for the HRD community, including scholars, practitioners, employees and managers in related HRD contexts.